Geochemistry of the Rio Espinharas hybrid complex, northeastern Brazil - Campos, T. F. C. (2002)
The Rio Espinharas pluton, northeastern Brazil, belongs to the shoshonitic series and consists mainly of syenogranite, quartz-monzonite and porphyritic quartz-monzonite, but diorite, quartz-monzodiorite, quartz-syenite and microsyenogranite also occur containing microgranular enclaves, except for the diorite. Most variation diagrams of rocks, amphiboles, biotites and allanites show linear trends, but K, Zr, Sr and Ba of rocks display curved scattered trends. The rocks ranging from diorite to syenogranite define a pseudo-errorchron and have similar REE patterns. Syenogranite and microsyenogranite are derived from two distinct pulses of granite magma with initial 87Sr/86Sr ratio of 0.7083±0.0003 and 0.7104±0.0007, respectively. Modelling of major and trace elements shows that the syenogranite evolved by fractional crystallization of plagioclase, microcline, edenite, biotite and titanite, whereas quartz-monzonite, porphyritic quartz-monzonite, quartz-monzodiorite and quartz-syenite resulted from simple mixing between an upper mantle-derived dioritic magma and the upper crust-derived syenogranite magma. Dioritic enclaves are globules of a mafic magma from the upper mantle.